Il ruolo delle donne nell’accoglienza e nell’inclusione dei migranti. Tratteggi di un’agency al femminile - Batholini, Ignazia (SocietàMutamentoPolitica, 2021)
Today, the identification of migrants with asylum seekers and the overestimation of inflows – also referred to as the “refugee crisis” – has meant that Italy, as a politically strategic borderland of Europe, coincides with a battleground between sovereign drives and solidarity tensions. If refugees are the most visible object of political contention, governance operated by Ngo’s and, more generally, by civil society, sees women in the front row in a battle aimed at re-humanizing politics. The clash, which lasted for weeks between Captain Rackete of Sea Watch 3 and Minister Salvini, did not only represent a confrontation between reception policies and rejection policies, between the dehumanization of the human and care as a distinguishing element of humanity, but a clash between political power and policy. In the following months, the honorary citizenship conferred on the captain in France reinvigorated the image of a female who pushes against “the established power”, referring to an ancestral symbolic of motherhood that becomes indiscriminate acceptance. The proposed article intends to explore the contribution of the female stakeholder and the elements that connote their gaze towards otherness and the support tools used, in order to focus on its distinguishing features of a female relationship in order to support migrant women victims of proximity violence.